Quilombola teaching practice: challenges and possibilities in times of pandemic - Ana Tereza Ramos de Jesus Ferreira; Hélio Rodrigues dos Santos; Geraldo Eustáquio Moreira (Universidade Federal do Norte do Tocantins, 2021)
We seek to investigate the challenges and possibilities of quilombola teaching practice and, in a more restricted way, reflect on the initial and continuing education of teachers, and identify advances in quilombola teaching practice in times of pandemic. Therefore, we adopted a qualitative and explanatory approach from the perspective of Historical-Cultural Theory to understand the reality and engender discussions on continuing education, use of technologies and mediation of the teaching and learning process. The information was collected through an online questionnaire using the Google Forms application, applied to 55 teachers from the Kalunga quilombola region in the state of Goiás. Our study showed the lack of investment in quilombola teacher training; the importance of teacher/student interaction; the collaborative teaching work enriches the pedagogical practice by providing the exchange of experiences and that the use of technological resources in education was essential, in order to ensure the continuity of the process, however, it was one of the factors responsible for the marginalization of teachers and students during teaching remote emergency.